Amylose-lipid complex as a measure of variations in physical, mechanical and barrier attributes of rice starch- ι -carrageenan biodegradable edible film. (December 2017) - Thakur, Rahul; Pristijono, Penta; Golding, John B.; Stathopoulos, Costas E.; Scarlett, Christopher J.; Bowyer, Michael; Singh, Sukhvinder P.; Vuong, Quan V.
Graphical abstract: Highlights: Rice starch-ι-carrageenan-fatty acid composite film blended with hydrophobic components was prepared. Lipid component improved the hygroscopic properties of rice starch films. Amylose-lipid complex was the major determinant of changes in film attributes. Sucrose fatty acid ester improved the physical, mechanical and barrier properties of starch-ι-carrageenan film. Abstract: Improvements in the hygroscopic properties of starch based films are important to strengthen their mechanical properties. The effects of different hydrophobic components-butyric acid (BA, C4:0), lauric acid (LA, C12:0), palmitic acid (PA, C16:0), oleic acid (OA, C18:1), stearic acid (SA, C18:0) and sucrose fatty acid ester (FAEs) on the rice starch (RS)-ι-carrageenan (ι-car) composite films were investigated. Scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) in combination with amylose-lipid complexing index (CI) were used to characterise the changes in structure and properties of edible films. The SEM results showed that the surface of films became smoother after the incorporation of fatty acids. Carbon-chain length was a major determinant of CI formation which further influenced the attributes of RS-ι-car films. The addition of FAEs to RS-ι-car improved film thickness, permeability, transparency, tensile properties (TS) and could be used to tailor biodegradable edible films with enhanced properties and future fruit coating applications.